PO 8269 Selection of seven-mutation PFCRT-PFMDR1 genotype after scaling-up seasonal malaria chemoprevention with sulphadoxine-pyrimethamine and amodiaquine in mali. (24th April 2019) - Maiga, Hamma; Bamadio, Amadou; Traore, Aliou; Diallo, Nouhoum; Diarra, Modibo; Sagara, Issaka; Niangaly, Hamidou; Coumare, Samba; Sangare, Boubou; Traore, Djibril; Vaillant, Michel; Dicko, Alassane; et al.
Abstract : Background: WHO recommended seasonal malaria chemoprevention (SMC) in 2012 for Sahel countries in Africa with the aim to reduce malaria among children under 5 years old by using sulphadoxine-pyrimethamine and amodiaquine (SP+AQ). This strategy was scaled up in Mali from 2012. The use of millions of doses of SP+AQ could generate potential Plasmodium falciparum resistance in mutant parasites. The aim of this study was to monitor the prevalence of Pfdhfr +Pfdhps +pfcrt + pfmdr 1 mutations in parasites infecting the target population. Methods: Two cross-sectional surveys were conducted before (August 2012, n=662) and after (June 2014, n=670) a pilot implementation of SMC in the health district of Koutiala. Children aged 3–59 months received 3 and 4 rounds of curative doses of SP+AQ over two malaria seasons in 2012 and 2013, respectively. Genotypes of P. falciparum Pfdhfr codons 51, 59, 108 and 164; Pfdhps codons 437 and 540, Pfcrt codon 76 and Pfmdr1 codon 86 were analysed by PCR on DNA of parasites from SMC population blood samples (after and before) and non-SMC patients aged 7 years or above (November 2014, n=500). Results: In the SMC population 191 and 85 children before and after SMC implementation, respectively, were included inthe molecular analysis. In the non-SMC patients, 220 weresuccessfully PCR analysed. In the SMC population, theprevalence of the six-mutation Pfcrt [ Pfdhfr-dhps quintuple + Pfcrt -76T] genotype increased significantly after SMC implementation, from 0.0% to 7.1% ( p=0.0008 ). The post-intervention prevalence of the six-mutation Pfmdr1 [ Pfdhfr-dhps quintuple + Pfmdr1– 86Y] and the seven-mutation Pfcrt +Pfmdr 1 [ Pfdhfr-dhps quintuple + Pfmdr1– 86Y+ Pfcrt -76T] genotypes were both 1.2% among the SMC population. No six-mutation and seven-mutation genotypes were observed among SMC population at baseline nor in the non-SMC patient population ( p=0.30 ). Conclusion: SMC increased the prevalence of the six-mutation Pfcrt genotype of P. falciparum that can lead to resistance in a population exposed to SMC with SP+AQ.